Straddling Economics and Politics Cross-Cutting Issues in Asia, the United States, and the Global Economy - Wolf, Charles Jr (RAND Corporation, 2002)
This collection of essays examines the case for and against globalization, the effects of U.S. economic and foreign policy, and numerous issues related to Asian economics and politics. Published in prominent journals and news media between 1996 and 2001, these cross-cutting essays are as relevant today as when they were first written. The author provides remarkable insight into the economic and military directions in which particular countries or regions are moving, and what these movements portend for the future.